PERSEPSI MASYARAKAT SEKITAR PERKEBUNAN KELAPA SAWIT PT SIBERIDA SUBUR RIAU TERHADAP KEBERADAAN HARIMAU SUMATERA (Panthera tigris sumatrae) - , GUSTI HERAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Riau Province was considered to hold the largest numbers of Sumatran tiger. However, massive forest conversion caused Sumatran tiger in the brink of extinction. Riau is also known as one of the top province in the Sumatraisland with high human-tiger conflict incidents.It has been one of the popular issues about conflict between Sumatran Tiger and human which happened in PT Siberia Subur, a private own of palm oil plantationin Riau Province. This study aims to investigate and describe this conflict in addition from society perception. This study used qualitative research method consisted by primary and secondary data. Primary data was obtained through semi-structure interview method with snowball sampling. Interviewee were came from society where the conflict occurred and primary data included knowledge and perspective of society on the conflict and Sumatran tiger existence. Society expectation was also investigated within this primary data. Secondary data was obtained from HTC (Human Tiger Conflict) team of WWF Indonesia, comprised data on tiger existence and other wild life surrounding the palm oil area. Results found three types of conflict attack to human, cattle predation, and settlement entrance. Perceptions toward Sumatran tiger were found vary both negative and positive. Opinion put tiger as protected species represented positive perception. They assumed the conflict occured due to human error and land conversion. The negative one defined the tiger as a threat to society life.